HIGH CAPACITY LITHIUM ION BATTERY ANODE BASED ON MODIFIED GEOTHERMAL SILICA WASTE - Haidar Hamid, Faiq
High areal capacity anodes play a crucial role in lithium-ion battery (LIB) applications requiring high energy density. This need can be met by constructing thick anode architectures to accommodate more active material per unit area, thereby enabling higher capacity storage. However, performance is often limited by slow electron/ion transport and poor cycle stability. This research addresses the challenges of high areal capacity anodes through the development of a nanofiber anode architecture synthesized via electrospinning. Geothermal silica waste (SiO?) is used as the active capacity-storing material, modified with cetrimonium bromide (CTAB) to stabilize the surface potential of silica nanoparticles, resulting in homogeneous dispersion in the polymer solution. Electrospinning produces nitrogen-doped carbon nanofibers encapsulating silica nanoparticles with a spindle-like structure (SiO?-CTAB@CNF). Unlike thick anode architectures from slurry coating methods, carbon nanofibers provide a conductive, interconnected network structure and efficient infiltration pathways for the electrolyte to penetrate the entire anode thickness. Consequently, despite a high mass loading per unit area (9.42 mg cm?²), the SiO?-CTAB@CNF anode achieves high areal capacity (~4 mAh cm?²), meeting the areal capacity targets of commercial lithium-ion batteries. Post-test analysis shows that the spindle-like structure helps reduce volume expansion of silica-based anodes, allowing the anode to retain 80% capacity (3.2 mAh cm?²) after 100 cycles. This study not only highlights the potential use of geothermal silica waste for sustainable lithium-ion battery technology but also demonstrates the benefits of fabrication methods for achieving high-performance anodes.